Recording vertical movement of a small Antarctic ice shelf by static GPS measurements (Hells Gate Ice Shelf - Victoria Land) - Bondesan, A.; Capra, A.; Gubellini, A.; Tison, Jean-Louis (1997)
info:eu-repo/semantics/published